Evaluation of a multiplex PCR assay for detection of respiratory viruses and Mycoplasma pneumoniae in oropharyngeal swab samples from outpatients. Issue 1 (19th October 2019) - Zhang, Ying; Cao, Lan; Xu, Zhi; Zhu, Pingting; Huang, Bing; Li, Kuibiao; Xu, Yang; Zhang, Zhoubin; Wu, Yong; Di, Biao
Abstract: Background: Respiratory viruses, such as influenza viruses, initially infect the upper airways but can manifest as severe lower respiratory tract infections in high‐risk patients with significant morbidity and mortality. For syndromic diagnosis, several multiplex nucleic acid amplification tests have been developed for clinics, of which SureX 13 Respiratory Pathogen Multiplex Kit (ResP) can simultaneously detect 13 pathogens directly from airway secretion specimens. The organisms identified are influenza virus A, influenza virus A pdmH1N1 (2009), influenza virus A H3N2, influenza virus B, adenovirus, boca virus, rhinovirus, parainfluenza virus, coronavirus, respiratory syncytial virus, human metapneumovirus, Mycoplasma pneumoniae, and Chlamydia . Methods: This study provides performance evaluation data of this assay by comparing with pathogen‐specific PCRs from oropharyngeal swab samples. Results: Ten pathogens were detected in this assay, of which rhinovirus, adenovirus, and influenza virus A pdmH1N1 (2009) were the most common. The overall agreement between the ResP and the comparator tests was 93.8%. The ResP demonstrated 86.5% agreement for positive results and 97.8% agreement for negative results. Conclusion: The ResP assay demonstrated a highly concordant performance comparing with pathogen‐specific PCRs for detection of respiratory pathogens in oropharyngeal swabs from outpatients and could aid in the diagnosis of respiratory infections in a variety of clinical scenarios.